Climate Actions and Stranded Assets: The Role of Financial Regulation and Monetary Policy - Francesca Diluiso; Barbara Annicchiarico; Matthias Kalkuhl; Jan C. Minx (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Limiting global warming to well below 20C may result in the stranding of carbon-sensitive assets. This could pose substantial threats to financial and macroeconomic stability. We use a dynamic stochastic general equilibrium model with financial frictions and climate policy to study the risks a low-carbon transition poses to financial stability and the different instruments central banks could use to manage these risks. We show that, even for very ambitious climate targets, transition risks are limited for a credible, exponentially growing carbon price, although temporary “green paradoxes” phenomena may materialize. Financial regulation encouraging the decarbonization of the banks' balance sheets via tax-subsidy schemes significantly reduces output losses and inflationary pressures but it may enhance financial fragility, making this approach a risky tool. A green credit policy as a response to a financial crisis originated in the fossil sector can potentially provide an effective stimulus without compromising the objective of price stability. Our results suggest that the involvement of central banks in climate actions must be carefully designed in compliance with their mandate to avoid unintended consequences.
Keywords: E50; H23; Q43; Q50; Q58; 330; climate policy; financial instability; financial regulation; green credit policy; monetary policy; transition risk